Analisis Risiko Kebangkrutan Bank Syariah dengan Metode Zscore (Studi Kasus pada Bank Umum Syariah di Indonesia periode 2008-2014) - Hasanatina, Foza Hadyu; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to examine islamic bank’s insolvency risk in Indonesia. Insolvency risk is measured by Zscore method. Factors are used in this study which influence islamic bank’s insolvency risk are fee based income, cost inefficiency, loan asset ratio and size. The population are islamic banks in Indonesia. This study use purposive sampling technique and select 5 (five) islamic bank for the sample. Characteristic of the sample are islamic banks in Indonesia which have periodic accounting data published by Otoritas Jasa Keuangan (OJK) in 2008-2014. The analisys method is multiple linier regression analysis. The result show that fee based income, cost inefficiency and loan asset ratio have significant and positive influence on islamic bank’s insolvency risk, but size has no significant influence on islamic bank’s insolvency risk. Judging by the value of adjusted R square was 31,3% which means the independent variabel is able to explain 31,3% variation of dependent variabel.